The relation between stimulated salivary flow and the temporal consumption experience of a liquid oral nutritional supplement. (1st November 2021) - Lester, S.; Hurst, K.; Cornacchia, L.; Kleijn, M.; Ayed, C.; Dinu, V.; Taylor, M.A.; Fisk, I.
Abstract: Use of oral nutritional supplements (ONS) in undernourished patients has proven clinical benefits, but this can be hampered by low adherence due to poor experience of palatability. Many patients, particularly older patients, experience hyposalivation which can cause taste changes and reduce the enjoyment of foods. The aim of this study was to investigate differences in the temporal consumption experience (comprising sensory perception, in-mouth aroma release and subjective appetite) of a clinically relevant portion of ONS, for groups differing in saliva flow rates (SFR). The SFR (mL/min) of thirty healthy individuals was measured on three occasions. This data was used to categorise individuals into three groups using quartile analysis: low flow (LF) (0.3–0.6 mL/min, n = 5), medium flow (MF) (0.7–1.2 mL/min, n = 16) and high flow (HF) (1.3–1.8 mL/min, n = 9). Over the consumption of eight 15 mL sips of ONS, individuals rated their sensory perception and subjective appetite perception using line scales. Additionally, in-mouth aroma release was measured for each sip, using atmospheric pressure chemical ionisation (APCI). Compared with the MF and HF group, the LF group reported a significantly greater increase of mouth-drying over increased sips (p = 0.02). The LF group also experienced significantly higher aftertaste perception (p < 0.001), and more intense in-mouth aroma release (p = 0.015), compared with the HF group. These findings occurred concurrently with relatively lower hunger sensations in the LF and MF group. Many patients who are prescribed ONS likely experience reduced salivary flow rates. The unique sensory experiences of these individuals should be considered in order to optimise palatability and nutritional intake. Highlights: A full portion of ONS was evaluated by three groups differing in saliva flow rates. A sensory profiling method captured perceptual differences over repeated sips. Mouth-drying built up most significantly for the low saliva flow group. Intensity of aftertaste and aroma release was highest in the low saliva flow group. Sensorial intensity of ONS may be associated with greater feelings of satiation.